Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fpubh.2020.608765
|View full text |Cite
|
Sign up to set email alerts
|

Can ACE2 Receptor Polymorphism Predict Species Susceptibility to SARS-CoV-2?

Abstract: A novel severe acute respiratory syndrome coronavirus, SARS-CoV-2, emerged in China in December 2019 and spread worldwide, causing more than 1.3 million deaths in 11 months. Similar to the human SARS-CoV, SARS-CoV-2 shares strong sequence homologies with a sarbecovirus circulating in Rhinolophus affinis bats. Because bats are expected to be able to transmit their coronaviruses to intermediate animal hosts that in turn are a source of viruses able to cross species barriers and infect humans (so-called spillover… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 89 publications
1
47
0
1
Order By: Relevance
“…During the past year, in vitro and in silico studies allowed to analyze interactions between SARS-CoV-2 and ACE2 (48)(49)(50). This has led many clinical research teams to hypothesize that soon after infection of people, SARS-CoV-2 is likely to trigger a dysfunction of ACE2 and subsequently variations in the balance between Ang II and Ang-(1-7), contributing to worsening hypertension and releasing of proinflammatory cytokines, especially IL-6, thereby accelerating -atherogenesis (35,51).…”
Section: Discussionmentioning
confidence: 99%
“…During the past year, in vitro and in silico studies allowed to analyze interactions between SARS-CoV-2 and ACE2 (48)(49)(50). This has led many clinical research teams to hypothesize that soon after infection of people, SARS-CoV-2 is likely to trigger a dysfunction of ACE2 and subsequently variations in the balance between Ang II and Ang-(1-7), contributing to worsening hypertension and releasing of proinflammatory cytokines, especially IL-6, thereby accelerating -atherogenesis (35,51).…”
Section: Discussionmentioning
confidence: 99%
“…Six RBD amino acids from the SARS-CoV S1 have been shown to be critical for binding to ACE2, namely L455, F486, Q493, S494, N501, and Y505 in SARS-CoV-2 (Andersen et al, 2020). The polymorphism of the ACE2 receptor at amino acid positions 31, 41, 82, 90, and 353 (with the most favorable residues being K31, Y41, N82, N90, K353) was used to estimate species susceptibility to SARS-CoV-2 (Devaux et al, 2021). Species such as Macaca mulatta, Felis catus, Rhinolophus sinicus, M. javanica, or Pelodiscus sinensis have been shown to be susceptible to SARS-CoV-2 infection.…”
Section: A Matter Of Compatibilitymentioning
confidence: 99%
“…Regarding SARS-CoV-2, several animal species were considered to be possible intermediaries, i.e. susceptible hosts which can be infected and are directly involved in the transmission to humans, besides pangolin, including cat, dog, cow, buffalo, goat, sheep, swine, civet, hamster, turtle, and pigeon (Devaux et al, 2021;Luan et al, 2020;Qiu et al, 2020).…”
Section: The Apparent "Multi-host Process" Of Coronavirus Emergencementioning
confidence: 99%
“…A number of recent computational studies comparing ACE2 protein sequences among different species or modeling the structure of the S protein:ACE2 complex to predict the breadth of potential viral hosts have suggested that, due to the high conservation of ACE2, many animals are vulnerable to infection by SARS-CoV-2 ( Ahmed et al, 2021 ; Damas et al, 2020 ; Devaux et al, 2020 ; Fischhoff et al, 2021 ; Huang et al, 2020b ; Kumar et al, 2021 ; Li et al, 2020b ; Liu et al, 2021 ; Melin et al, 2020 ; Rodrigues et al, 2020 ). Humans are likely to come into contact with 26 of these species in domestic, agricultural, or zoological settings ( Lam et al, 2020a ) ( Figure 3 ).…”
Section: Sars-cov-2 Phylogenetic Prediction Of Susceptible Speciesmentioning
confidence: 99%
“…In contrast, the highest similarity of the relative synonymous codon usage of SARS-CoV-2 and snakes led to the latter being hypothesized as a potential viral host ( Ji et al, 2020 ). However, bioinformatics approaches that are based on the analysis of their ACE2 receptor ( Luan et al, 2020 ; Zhang et al, 2020a ) argued against this assumption ( Devaux et al, 2020 ).…”
Section: Sars-cov-2 Phylogenetic Prediction Of Susceptible Speciesmentioning
confidence: 99%